Perancangan Software Requirements Specification (SRS) Sistem Informasi Banking Kartu Kredit - Fuad Mumtaz (Jurnal Informatika dan Bisnis, 2013)
With the development of business and the needs for a credit card is a credit card by the wider community also needed a system that is able to support stakeholders in the business.In this paper will be made an Application Credit Card Banking Information System which is an integrated information system that is made for bank credit card services provider covering the prospective customer application process, recording customers' credit card usage transactions, billing penggunaa credit cards to customers, processing customer payments the credit card billing and payment process to the card associations. So that other stakeholders such as merchants and acquirers are not included in this application.Application Software Requirement Specification (SRS) will have several benefits which can help users of bank credit card providers are divided into each unit includes functions such as customer service Unit Accounts Officer, Unit A / R, Unit A / P and Billing Unit Officer (Billing) to be used in terms of requirements to implement features on Information Systems Banking Credit Card.